ANALISIS PENGARUH ENSO 1997 TERHADAP CURAH HUJAN 1981-2010 DI PALEMBANG, BANJARMASIN DAN TABING - Nizar Manarul Hidayat (Republic of Indonesia Defense University, 2022)
This study focused on the influence of El Niño and La Niña on 30 years of rainfall in Tabing, Palembang, and Banjarmasin. 1997-1998 and 1982-1983 period get some particular attention because it is assumed as an important climatological event. Rainfall data from the period 1981-2010 are used. ENSO activities have been analyzed by comparing monthly rainfall with Nino 3.4 index. During El Niño, the monthly rainfall of Banjarmasin and Palembang tends to fall by more than 50%. While in the Tabing down reach 36.83%. At La Niña conditions it is likely to have a positive impact on monthly rainfall in the three areas of which more than 40%. Rainfall in Banjarmasin increased to 122 mm in July. While the area of Tabing and Palembang increased 163.3 mm in September. Correlation analysis between monthly rainfall and Nino 3.4 index during the period revealed that ENSO activities gave a negative impact on Banjarmasin monthly rainfall with the highest correlation coefficient occurred in October, reaching -0.64. Seasonal analysis shows no anti-theory because of the increasing dry period on El Niño and increasing uncertainty on the wet period on La Nina.